New Zealand : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
New Zealand's economy continued to grow at a moderate rate, in part reflecting the effects of the recent drought and inflation. The macroeconomic policy has been framed to absorb adverse shocks with flexible exchange rates to serve as buffer. The planned pace of deficit reduction is balanced between sustaining aggregate demand and limiting public debt growth. Recent stress tests also showed that major banks could withstand a sizable shock to output, terms of trade, rising unemployment, and a fall in property prices.